INTO THE FICTIONAL WOODS OF TRISTRAM SHANDY: READER AND NARRATOR BETWEEN THE LINES - Trigo, Aline Candido [UNESP]; Brito, Luciana (Univ Federal Santa Catarina, Programa Pos-graduacao & Letras-ingles, 2021)
This work analyzes the figurations of the reader in Tristram Shandy, by Laurence Sterne, based on the ideas of Umberto Eco, Gerard Genette, and Maurice Blanchot, which focus on the relationship between narrator and reader, and the aesthetic effect resulting from formal techniques. In face of a self-conscious narrator-author-character, the play with the limits of reality and imagination are frequent, and it challenges the most diverse kinds of readers even in contemporaneity. Reflecting about the act of reading, the text performs the actions of multiple kinds of readers through the narrator's discourse. Considered by Virginia Woolf the forerunner of the modern novel, Sterne's work causes discrepancy regarding the interpretation of its form as it will be discussed here, by the point of being sometimes better comprehended by shandean writers that took the novel as a reference, re-signifying the mimesis and the literary form.
Keywords: Tristram Shandy; Narrator; Reader; Narratee